Development and immunodiagnostic application of 30 kDa monoclonal antibody against coproantigens of Strongyloides in animal model - Abdulhaleam, Noor (2017)
Intestinal strongyloidiasis is usually underdiagnosed and the available parasitological techniques such as stool examinations based on Baermann or agar plate cultures are time-consuming, which involved three specimens collected at the different time intervals for more accurate and sensitive application. The current available preferred serological technique for diagnostic of intestinal strongyloidiasis shows the crossreaction with other intestinal helminths. This preliminary study is aimed to produce and evaluate monoclonal antibody against the coproantigen of Strongyloides ratti in the animal model. Strongyloides ratti infection model was established and maintained in immunosuppressed Sprague Dawley rats. The saline extract protein from the infective larvae (iL3) was used as antigens for the immunisation of BALB/c mice. The splenocytes harvested from the immunised mice were fused with myeloma (SP2/0) cells for hybridoma production. Supernatants from the positive hybrids were screened by indirect ELISA. The purified IgG2b MAb was characterised by western blots and evaluated in sandwich-ELISA for reactivity against the homologous and heterologous antigens which include Toxocara canis, Toxocara cati, Ancylostoma caninum and Ascaris suum. An IgG2b MAb that recognises 30 kDa molecular weight proteins associated with strongyloidiasis and a cross-reaction with a 30 kDa for Ancylostoma caninum were observed. The IgG2b MAb was recognised by two Strongyloides ratti antigens and saline extract antigen of Ancylostoma caninum but did not react with other heterologous antigens in both assays. The antigen detection limit by sandwich ELISA was 75 ng/mL. Seventeen out of the twenty strongyloidiasis experimentally infected rat faeces (85%) evaluated for coproantigen using the IgG2b MAb have shown antigen-positive reactions in sandwich-ELISA. Similarly, only Ancylostoma caninum from dog faeces were reactive against the IgG2b MAb from all samples tested for cross-reactivity. This study concluded that the IgG2b MAb produced was able to detect Strongyloidiasis and Ancylostomiasis in animal models.